Statement of the Second International Exercise-Associated Hyponatremia Consensus Development Conference, New Zealand, 2007 - Hew-Butler, T.; Ayus, J. C.; Kipps, C.; Maughan, R. J.; Mettler, S.; Meeuwisse, W. H.; Page, A. J.; Reid, S. A.; Rehrer, N. J.; Roberts, W. O.; Rogers, I. R.; Rosner, M. H.; et al. (Clinical Journal of Sport Medicine, 2008)
The Second International Exercise-Associated Hyponatremia (EAH) Consensus Development Conference convened in Queenstown, New Zealand (November 2007) with a panel of eighteen international experts. This conference utilized the United States National Institute of Health (NIH) Consensus Conference protocol and was deliberately free from commercial sponsorship. The delegates represented seven countries and eight medical and scientific sub-specialties pertaining to exercise physiology, sports medicine, water metabolism, and body fluid homeostasis. The primary goal of the panel was to review the existing data on EAH and update the 2005 Consensus Statement. This document serves to replace the 1st International EAH Consensus Development Conference Statement. The purpose of this update is to summarize the most current information on the prevalence, nature and treatment of EAH for medical personnel, athletes, and the greater public and to curtail the morbidity andmortality associated with the disorder. The panel strived to clearly articulate what we agreed upon, debate issues that we did not agree upon, and describe in detail what we did and did not know, including minority viewpoints that were supported by clinical and experimental data. The following statement is a concise summary of the data synthesized by the 2007 EAH Consensus Panel and represents an evolution of the most current knowledge on EAH. Further updates will be required as the understanding of EAH advances.